Analysis of Numerical Literacy Ability of Junior High School Students viewed from Gender Difference using Minimum Competency Assessmen - Kasanah, Hidayatun; Rahayu, Puji (Jurnal Pendidikan MIPA, 2022)
This study aims to describe the numeracy literacy skills of junior high school students in terms of gender. Data collection techniques in the form of test questions and interviews. The results of this study indicate that male students are able to use knowledge to solve problems, interpret problems and use, write down steps and use strategies in solving problems, use models and explanations in solving problems partially correctly, models to solve situations that complex and complicated questions partially correct, and have not been able to use reasoning in solving problems. While the numeracy literacy skills of female students are able to use knowledge to solve problems, interpret problems and use formulas partially correctly, write down steps and use strategies to solve problems partially correctly, models and explanations in solving problems partially correctly, models to solve complex situations and complicated problems partially correctly, and use reasoning in solving problems partially correctly. Keywords: numerical literacy, gender, minimum competency assessment. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1181-1194